Factors related to HIV infection and sexual patterns among males attending STD/AIDS centers in Thailand, 1996 - Suchada, Juntasiriyarkorn
During the Fourteenth National HIV Sentinel Serosurvey, June to July, 1996, males attending the STD/AIDS Centers, Center 2 to Center 12, of the Royal Thailand Ministry of Public Health, were asked to fill up the confidential self-administered questionnaire. Blood sample was also drawn for HIV and VDRL testing. Medical diagnosis was reviewed. Sexual patterns were described and the factors correlated with HIV infection were identified. There were a total of 941 males who participated in this study. Participant were predominantly middle-aged adults with an average age of 31 years educated only up to the primary level, married, worked as laborers, and came from the low economic status. The geographical variation of demographic characteristics and sexual patterns was not documented. The mean age at first sexual intercourse was 18 years. Most of them had their first sex with female commercial sex workers without using condom. The majority of the respondents reported having sexual intercourse outside their marriage and less than half of them reported consistency of using condom. More than 50 percent of the men reported having engaged in commercial sex in the past year. Vaginal sexual intercourse was the major sexual act. Less than 10 percent of the respondents reported having engaged in same gender sexual intercourse in the past year. The following 4 variables were found to be significantly associated with HIV infection in the univariate analysis: received tatoo (OR: 2.36; 95 CI: 1.09-5.04), injecting drug use (OR: 5.03; 95 CI: 1.12-17.45), sex with male (OR: 4.77; 95 CI: 1.46-13.41) and having CSW regular partner (OR: 18; 95 CI: 3.99-81.30). However, sex with men was the only independent variable found to be statistically associated with HIV infection with the adjusted odds ratio of 9.20 (95 CI: 3.082-27.45). The majority of Thai males had alarmingly high-risk behaviors, which were aggravated by inconsistent use of condom and having sex with a female sex worker. Increasing condom use and modifying the risky behaviors should be the immediate goals of the HIV/AIDS prevention and control programmes.